2015
DOI: 10.3109/08880018.2015.1079756
|View full text |Cite
|
Sign up to set email alerts
|

Impairments of Lower Extremity Muscle Strength and Balance in Childhood Cancer Patients and Survivors: A Systematic Review

Abstract: This review aims to summarize the evidence for impairments of muscle strength and balance during and after treatment for childhood cancer. Thirty-two articles, identified in scientific databases by means of a structured search for investigations of muscle strength and balance in pediatric cancer patients and survivors, are evaluated. A summary of results is given with respect to matching reporting items to provide a qualitative analysis of the evidence. The majority of the studies reached a level 3 rating acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
41
0
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 60 publications
3
41
0
7
Order By: Relevance
“…The present results are similar to those of two previously published reviews on balance in pediatric cancers in general. 25,26 In both reviews, the authors concluded that although there was some evidence to support childhood cancer survivors having diminished balance abilities in comparison with healthy peers, there is a need for further studies with greater statistical power.…”
Section: Discussionmentioning
confidence: 99%
“…The present results are similar to those of two previously published reviews on balance in pediatric cancers in general. 25,26 In both reviews, the authors concluded that although there was some evidence to support childhood cancer survivors having diminished balance abilities in comparison with healthy peers, there is a need for further studies with greater statistical power.…”
Section: Discussionmentioning
confidence: 99%
“…Physical function testing in children with cancer is gaining increasing interest as reports of physical function impairment during and after treatment become more prevalent. Function disabilities include reductions in cardiopulmonary function, muscle strength, balance, and general physical weakness, that impact quality of life . The existing topic‐related studies include limited numbers of children (n = 15–128) as well as restricted diagnostic groups and inclusion criteria.…”
Section: Introductionmentioning
confidence: 99%
“…Cyclophosphamide, methotrexate (MTX), vincristine (VCR), and other chemotherapeutic agents are responsible for several side effects on cognitive, neurological, and motor functions, which negatively impact patients’ development. Patients with leukemia and lymphoma are at risk for developing complications such as decreases in muscular strength, impaired gross and fine motor skills, osteonecrosis, and fatigue . These outcomes are evident at diagnosis and especially at an early stage of treatment .…”
Section: Introductionmentioning
confidence: 99%